Analysis of Pile Behavior Adjacent to a Deep Excavation - Nishanthan, R.; Liyanapathirana, D.S.; Leo, C.J. (University of Western Sydney, 2012)
In urban areas, excavations for cut-and-cover tunnels and basement construction cause detrimental effects on adjacent piles. This paper presents a case study of a deep excavation carried out adjacent to a group of piles consisting of 22 m long step tapered piles. The pile group was located 0.6 m behind a temporary sheet pile wall. The excavation was primarily carried out through the layered sandy soils and supported by a sheet pile. The retaining wall system of the 15 m deep excavation was supported by tie back anchors at three levels. Finite element modelling is used to simulate the staged construction sequence, which involves excavation and installation of the prop system. Constitutive behaviour of the soil is modelled using an elasto-plastic model due to the limited amount of material properties available for the site. The pile deflection and the soil movements from two and three dimensional finite element analyses are compared with field data to determine the most appropriate way of modelling the pile group behaviour adjacent to an excavation. In urban areas, excavations for cut-and-cover tunnels and basement construction cause detrimental effects on adjacent piles. This paper presents a case study of a deep excavation carried out adjacent to a group of piles consisting of 22 m long step tapered piles. The pile group was located 0.6 m behind a temporary sheet pile wall. The excavation was primarily carried out through the layered sandy soils and supported by a sheet pile. The retaining wall system of the 15 m deep excavation was supported by tie back anchors at three levels. Finite element modelling is used to simulate the staged construction sequence, which involves excavation and installation of the prop system. Constitutive behaviour of the soil is modelled using an elasto-plastic model due to the limited amount of material properties available for the site. The pile deflection and the soil movements from two and three dimensional finite element analyses are compared with field data to determine the most appropriate way of modelling the pile group behaviour adjacent to an excavation.
Keywords: Finite element modelling; Deep excavation; Pile response; Construction sequence; Soil movements